Are multiple views superior to a single view when teaching hip surgery? A single-blinded randomized controlled trial of technical skill acquisition - Wang,H; Sugand,K; Newman,S; Jones,G; Cobb,J; Auvinet,E (PLoS ONE, 2019)
s Metrics Comments Media Coverage Abstract Introduction Materials and methods Results Discussion Conclusion Supporting information References Reader Comments (0) Media Coverage (0) FiguresAbstractPurposeSurgical education videos currently all use a single point of view (POV) with the trainee locked onto a fixed viewpoint, which may not deliver sufficient information for complex procedures. We developed a novel multiple POV video system and evaluated its training outcome compared with traditional single POV.MethodsWe filmed a hip resurfacing procedure performed by an expert attending using 8 cameras in theatre. 30 medical students were randomly and equally allocated to learn the procedure using the multiple POV (experiment group [EG]) versus single POV system (control group [CG]). Participants advanced a pin into the femoral head as demonstrated in the video. We measured the drilling trajectories and compared it with pre-operative plan to evaluate distance of the pin insertion and angular deviations. Two orthopedic attendings expertly evaluated the participants’ performance using a modified global rating scale (GRS). There was a pre-video knowledge test that was repeated post-simulation alongside a Likert-scale questionnaire.ResultsThe angular deviation of the pin in EG was significantly less by 29% compared to CG (p = 0.037), with no significant difference in the entry point’s distance between groups (p = 0.204). The GRS scores for EG were 3.5% higher than CG (p = 0.046). There was a 32% higher overall knowledge test score (p<0.001) and 21% improved Likert-scale questionnaire score (p = 0.002) after video-learning in EG than CG, albeit no significant difference in the knowledge test score before video-learning (p = 0.721).ConclusionThe novel multiple POV provided significant objective and subjective advantages over single POV for acquisition of technical skills in hip surgery.